History of Indian literature in english - Ravi Nandan Sinha (B R Publishing corporation, 2019)
B.R. Publishing Corporation, 2019. Hardcover. Condition: New. 1st Edition. History of Indian Literature in English is a concise yet comprehensive account of the origin and growth of various literary trends in Indian Literature in English over the last two centuries. In a very lucid style, it analyzes the various literary and non-literary influences on this literature. It discusses the landmark authors under four subheads: poetry, drama, fiction and prose. The book also tries to place those authors in the literary traditions to which they belong.